Evolução da desigualdade da distribuição de renda no Brasil, grandes regiões e estados do Nordeste entre 2001 e 2008. - Miranda, Sérgio Gonçalves de (2010)
This study uses data from the Statistical Office’s annual national sample survey of Brazil (PNAD) to elucidate inequality of income distribution behavior in the Northeastern states using the Gini index for the years of 2001 and 2008 as standards. It has been concluded that income distribution in Brazil had been improved in the five large country regions and nine Northeastern states in this period. Using the methodology proposed by Hoffmann (2006) to decompose the Gini index, the contribution for each portion of family income per capita for the fall of the Gini index have been evaluated. It has been estimated that the major cause for the drop in inequality was the income from employment contributing 67% in the Brazilian fall and 46% in the Northeastern. This primacy of labor income occurred in five Northeastern states: Rio Grande do Norte (66.92%), Ceará (62.56%), Pernambuco (58.76%), Maranhão (43.89%) and Sergipe (34,58%). In Piauí (63.31%) and Bahia (50.74%), the portion that contains interest income, applications and official transfers were the main responsible for the reduction in income inequality. From another standpoint, in Alagoas and in Paraiba the largest contribution came from retirement income, with percentage of 119.59% and 60.27% stake, respectively. Although labor income have been the one with the largest contribution to the fall of income concentration in the Northeast, one can not disregard the weight of income arising from interest, applications and official transfers in the process, since the average contribution of this installment in the fall of the Gini in the region is more than double of national participation. This high contribution occurs even with a relatively low participation in the formation of income, which reaches a peak of 4.22% of family income per capita the state of Alagoas.